A Red Brick Wall: Anti-Immigrant Rhetoric in a Residence Hall Environment. (December 2017) - Duran, Antonio
This case study was developed for leadership courses in higher education and student affairs programs, specifically those looking at issues of multiculturalism and social justice. It features a residence hall at a predominantly White institution with a student population and a surrounding town that largely reflect conservative views. Specifically, this case asks educators to think about how they would react to a series of events that indicate xenophobic, racist nativist, and anti-immigrant rhetoric, culminating in a physical barrier being built outside of the hall to symbolize a divide between students. Both the Residence Hall Director and Assistant Residence Hall Director play a key role in responding to these incidents as they hope to strengthen their residence hall community in light of the negative events.